Antimicrobial efficacy of photosensitized nanoparticles, diode laser, conventional, and sonic irrigation systems against enterococcus faecalis in root canals - An in vitro study - Ananya Sharma; Rohit Kochhar; Manju Kumari (Wolters Kluwer Medknow Publications, 2022)
Aim: This study aims to evaluate and compare the antimicrobial effect of Photosensitized Nanoparticles, Diode Laser (DL), and Conventional and Sonic Irrigation Systems against Enterococcus faecalis in root canals - An in vitro Study. Materials and Methods: The root canals of 104 extracted human single-rooted teeth were prepared, and E. faecalis was incubated in the root canals for 1 week. The teeth were randomly divided into four experimental groups and one control group (n = 20): No treatment was done, sodium hypochloride (NaOCl) group (n = 20): Canals irrigated with5 ml of 2.5% NaOCl for 60 s, NaOCl and Endoactivator group (n = 20): Canals irrigated with 5 ml of 2.5% NaOCl for 60 s followed by activation of NaOCl with Endoactivator for 30 s, NaOCl and 910 nm DL group (n = 20): (1 W 5 times for 5 s) canals irrigation with5 ml of 2.5% NaOCl for 60 s followed by Photodynamic Therapy (PDT) with 910 nm DL, silver nanoparticles (AgNPs)/Indocyanine green (ICG)/DL group (n = 20): DL modified PDT with 5 min of irrigation with 5 mL AgNPs (100 ppm)/ICG/910 nm DL (200 mW, 30 s). A reduction in colony count was assessed by counting colony-forming units by Digital Colony Counter. Results: Significant reductions were noted in E. faecalis colony counts in all groups (P < 0.05). The greatest reduction in colony count (99.93%) was noted in the NaOCl and DL group followed by NaOCl and Endoactivator group; however, the differences in this respect between the AN/ICG/DL group and NaOCl group were not significant (P > 0.05). Conclusions: NaOCl and 910 nm DL were more successful in reducing the number of E. faecalis colony counts followed by NaOCl and Endoactivator group but it can also be concluded that PDT with ICG, an 910 nm DL, and AgNPs has the potential to be used as an adjunct for disinfection of the root canal system.